A survey of rose viruses in England. (June 2023) - Vazquez-Iglesias, Ines; Boonham, Neil; Robinson, Rebekah; Clover, Gerard R.G.; Fox, Adrian
Abstract: Roses ( Rosa spp.) are valuable ornamental shrubs grown worldwide. Despite the importance of their cultivation, the large contribution they make to the United Kingdom (UK) garden industry, and the global spread of rose viruses, they have not been studied in detail in the UK since the 1980s. In this study, a survey of rose viruses in England was performed using molecular and serological methods. The aims of the study include an update on the presence and incidence of rose viruses, analysis of symptoms and mixed infections, and identification of the viruses involved in rose mosaic disease, one of the most common diseases in roses worldwide. Previously reported viruses in the UK were found during this study, including strawberry latent ringspot virus (family Secoviridae ), arabis mosaic virus (genus Nepovirus ), and prunus necrotic ringspot virus (genus Ilarvirus ), but also two commonly known viruses were found for the first time infecting roses in the UK (cucumber mosaic virus [genus Cucumovirus ] and tomato spotted wilt virus [genus Orthotospovirus ]). This work led to first records for the UK of two viruses, rose cryptic virus-1 (genus Alphapartitivirus – pending approval by the International Committee on the Taxonomy of Viruses), and rose spring dwarf-associated virus (genus Luteovirus ). Here, the presence and distribution of each of these viruses are reported. Highlights: Study of rose viruses in England using serological and molecular methods. Detection of ArMV, PNRSV, and SLRSV, previously recorded in the country. ArMV, SLRSV and RoCV1 identified showed the highest prevalence in the UK. First record of CMV and TSWV infecting roses in the UK. RRV was not detected during this survey.